2020
DOI: 10.1016/j.sjbs.2020.09.023
|View full text |Cite
|
Sign up to set email alerts
|

UNC5A, an epigenetically silenced gene, functions as a tumor suppressor in non-small cell lung cancer

Abstract: UNC5A has been reported to be related with human cancers. However, the function and mechanism in non-small cell lung carcinoma (NSCLC) remains unknown. We analyzed two NSCLC cell lines (A549 and H157), one normal human bronchial epithelial cell line (BEAS-2B) and the tissues of NSCLC. We used quantitative real-time PCR (qRT-PCR), western blot and immunohistochemical (IHC) staining to examine the expression of UNC5A. Methylation status of the UNC5A promoter was analyzed using methylation-specific PCR (MSP) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…We found that Unc5a and Eif4b mRNA expression were positively linked to the arrest in G1/G0 phase and changes in hr-tPA production ( Table 2 ). Unc5a acts as a tumor suppressor of different cancers through inhibition of cell growth [ 33 , 34 ]. Eif4b is a key piece for mRNAs translation into proteins and also regulates the translation of proliferative and pro-survival mRNAs [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found that Unc5a and Eif4b mRNA expression were positively linked to the arrest in G1/G0 phase and changes in hr-tPA production ( Table 2 ). Unc5a acts as a tumor suppressor of different cancers through inhibition of cell growth [ 33 , 34 ]. Eif4b is a key piece for mRNAs translation into proteins and also regulates the translation of proliferative and pro-survival mRNAs [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…To explore which potential miR-214 target genes could be involved in this apoptotic response, we performed RNA sequencing analysis of miR-214 mimic-transfected, DMBA-treated equine MDECs which revealed 100 potential gene targets of miR-214-3p. We predicted UNC5A would be involved, based on (i) its role in mediating apoptosis 29 , 36 , 37 ; (ii) the exceptionally strong miR-214-3p binding site of the 3’ untranslated region (UTR) of UNC5A , consisting of 13 consecutive base pairings from the 5’-end of the miRNA; and (iii) the UNC5A ligand, netrin-1 (NTN1) gene being a proven target of miR-214-3p in bladder cancer cells 38 . Downregulation of NTN1 was not detected in our RNA sequencing screen, suggesting that this ligand is not regulated by miR-214 in equine MDECs, and reinforcing the notion that miRNA activity varies according to species, cell type, and/or sub-cellular location 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Unc-5 netrin receptor A (UNC5A), encoding an axon-guiding molecule, is located on the 5q35 chromosomal region and functions as a receptor of netrin family (including netrin-1, and netrin-3) with key roles in neuronal development and differentiation [ 14 , 15 ]. Previous studies found that the UNC5A belong to dependence receptors, and its most notable functional feature is that UNC5A can act as a double-edged sword, its function depending on the availability of the ligands.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Silu Ding and colleagues found lowered UNC5A expression levels in non-small cell lung carcinoma compared to adjacent normal tissues. Moreover, they knocked down the UNC5A gene in human lung cancer cell lines and found enhanced cellular proliferation, invasion, migration, and apoptosis, while UNC5A overexpression derived opposite outcomes [ 14 ]. Another report illustrated that p53 can activate UNC5A expression by binding to the gene’s promoter, and overexpression of UNC5A greatly inhibits the colony formation ability of glioblastoma cells [ 20 ].…”
Section: Introductionmentioning
confidence: 99%